Optomechanical crystal nanobeam cavity with high optomechanical coupling rate. (26th February 2015) - Li, Yongzhuo; Cui, Kaiyu; Feng, Xue; Huang, Yidong; Huang, Zhilei; Liu, Fang; Zhang, Wei
Abstract: An optomechanical crystal nanobeam cavity, only by increasing the radius of air holes in the defect region, is proposed and optimized for a high optomechanical coupling rate. In our proposed cavity, the photonic and phononic defect modes are simultaneously confined by each corresponding bandgap, and the overlap of the optical and mechanical modes can be improved simply by adjusting the radius of the air holes. Accordingly, an optomechanical coupling rate ( g ) as high as 1.16 MHz is obtained, which is the highest coupling rate among the reported optomechanical crystal cavities. What's more, the proposed cavity also exhibits a high mechanical frequency of 4.01 GHz and a small effective mass of 85 fg for the fundamental mechanical mode.